fisheries-research 2019
DOI: 10.35841/fisheries-research.3.1.7-17
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of catch composition and economic analysis of monofilament and multifilament under-meshed gears (Ngongongo) at Likoma Island, Lake Malawi

Abstract: The study was conducted to assess catch composition and economic analysis of monofilament and multifilament under-meshed gillnets (Ngongongo) from March to April 2018 around Likoma Island, Lake Malawi. Catch efficiency for targeted fish species in monofilament gillnets showed that catch per unit effort (CPUE) was three times higher than that of multifilament gillnets for Copadichromis spp. (402.2 Kg, 43.3%), Opsaridium microcephalum (315.47 Kg, 34.6%), Rhamphochromis spp. (26.2 Kg, 2.8%), Bagrus meridionalis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…There are concerns about possible increases in catching efficiency, considering several studies on other species have demonstrated relatively greater (up to ∼1.5-2.7×) catch-per-unit-of-effort (CPUE) among gillnets made from monofilament (e.g. Washington, 1973;Balik & Çubuk, 2000Balik & Çubuk, , 2004Thomas et al, 2003;Simasiku et al, 2017;Richard Winston et al, 2019). Such concerns are not only directed towards S. commerson but also several other retained (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…There are concerns about possible increases in catching efficiency, considering several studies on other species have demonstrated relatively greater (up to ∼1.5-2.7×) catch-per-unit-of-effort (CPUE) among gillnets made from monofilament (e.g. Washington, 1973;Balik & Çubuk, 2000Balik & Çubuk, , 2004Thomas et al, 2003;Simasiku et al, 2017;Richard Winston et al, 2019). Such concerns are not only directed towards S. commerson but also several other retained (e.g.…”
Section: Introductionmentioning
confidence: 99%